Analysis of Numeracy Literacy Ability of 11th Grade Students on Reaction Rate Material at SMAN 1 Grogol - Pertiwi, Niken Yuhana; Ardhana, Ivan Ashif (IJCER (International Journal of Chemistry Education Research), 2025)
Numeracy literacy skills are abilities that need to be trained and developed, focusing on understanding concepts and mathematical calculations as well as their application in the process of contextual problem-solving. Specifically, the level of numeracy literacy in each school in Indonesia has not yet been identified, particularly in the context of reaction rates in chemistry, which is rarely analyzed. Therefore, this study aims to describe the overall level of students' numeracy literacy on the topic of reaction rates, based on numeracy literacy indicators, gender, and cognitive aspects in Bloom's taxonomy. This research employs a descriptive quantitative approach, involving 60 students as subjects. The research instrument consisted of 20 essay questions about numeracy literacy skills related to the topic of reaction rates, with a reliability of 0.817, categorized as very high. The research results indicate that, overall, the level of numeracy literacy on the topic of reaction rates remains low, with a percentage of 37.74%. Based on indicators, (1) the ability to analyze information in the form of tables, graphs, diagrams, and charts reached 47.09%; (2) the use of numbers and symbols was 36.07%; (3) interpreting analysis results to make decisions was 34.28%. Based on gender, male students achieved a rate of 39.61%, while female students achieved a rate of 37.06%. Based on cognitive aspects in Bloom's Taxonomy, C4 (analyzing) achieved the highest score of 50.44%, followed by C5 (evaluating) at 32.08%, C3 (applying) at 29.70%, and C6 (creating) at 21.50. These findings emphasize the importance of improving numeracy literacy skills in Indonesia, especially in chemistry education. These results can also serve as a basis for teachers in designing learning strategy policies by integrating numerical skills, data interpretation, and logical reasoning to enhance students' numeracy literacy in chemistry learning more broadly.